Beispiel Nr: 07
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ -2 x +2 + 4 z=0\\ 4 x -\frac{1}{2} y + 2 z=5\\ 4 x -2 y + -1 z=8\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} -2x+2y+4z=0 \\ 4x-\frac{1}{2}y+2z=5 \\ 4x-2y -z=8 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & 2 & 4 & 0 \\ 4 & -\frac{1}{2} & 2 & 5 \\ 4 & -2 & -1 & 8 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot (-2)\text{-Zeile}1\cdot 4 \\z2s1=4\cdot -2-(-2)\cdot 4 =0 \\ z2s2=(-\frac{1}{2})\cdot -2-2\cdot 4 =-7 \\ z2s3=2\cdot -2-4\cdot 4 =-20 \\ z2s4=5\cdot -2-0\cdot 4 =-10 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & 2 & 4 & 0 \\ 0 & -7 & -20 & -10 \\ 4 & -2 & -1 & 8 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-2)\text{-Zeile}1\cdot 4 \\z3s1=4\cdot -2-(-2)\cdot 4 =0 \\ z3s2=(-2)\cdot -2-2\cdot 4 =-4 \\ z3s3=(-1)\cdot -2-4\cdot 4 =-14 \\ z3s4=8\cdot -2-0\cdot 4 =-16 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & 2 & 4 & 0 \\ 0 & -7 & -20 & -10 \\ 0 & -4 & -14 & -16 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-7)\text{-Zeile}2\cdot (-4) \\z3s2=(-4)\cdot -7-(-7)\cdot (-4) =0 \\ z3s3=(-14)\cdot -7-(-20)\cdot (-4) =18 \\ z3s4=(-16)\cdot -7-(-10)\cdot (-4) =72 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline-2 & 2 & 4 & 0 \\ 0 & -7 & -20 & -10 \\ 0 & 0 & 18 & 72 \\ \end{array} \\ \\ z=\frac{72}{18}=4\\y \cdot (-7)+(-20)\cdot4=(-10)\\y= -10\\x\cdot (-2)+2\cdot-10+4\cdot4=0\\x= -2\\L=\{-2/-10/4\}$